Experimental Studies on Waste Plastic Fibre Reinforced Concrete Using M-Sand as Fine Aggregate - A, Tamilarasan; V, Sumitha; R, Abinayakeerthana (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Concrete is the main construction materialin the world. It consist of cement, fine aggregate, coarse aggregate and water as main ingredients. Now days due to high global consumption of natural sand, sand deposit are being depleted and causing serious threat to environment as well as society. River sand is becoming a scarce commodity and hence an exploration alternative to it has become imminent. Manufactured sand is the good alternative to river sand and it is purposely made, fine crushed aggregate produced under controlled conditions from a suitable sand source rock. Plastics are non biodegradable common environmental polluting materials. These are going to affect the fertility of soil. In present study the detailed experimental investigation is carried out on plastic fibre reinforced concrete by partial replacement of  natural sand by manufactured sand with different  percentages( 0%, 20%, 40%, 60%,80%,100%) and adding fixed percentage (0.5% of weight cement)) of plastic fibres. The mechanical properties of concrete like compressive strength, tensile strength and flexural strength are studied here